The Role of The Village Consultancy Agency (BPD) in Implementing Village Autonomy - Firman H (Journal of Indonesian Scholars for Social Research, 2022)
The Village Consultative Body is a community consultative institution in the village, a working partner of the village head in administration, development, and society, which functions as a legislative, supervisory body. It accommodates and channels the aspirations of the community. The research method is exploratory research, namely by focusing on specific objects exploring something related to general statements—the number of samples as many as 18 people or sample Saturated (Total Sample). The results of this study are 1) Village Autonomy is essentially carried out jointly between the government community. Still, the ability of the village government as a development initiator, communicator, and manager (leader) in the implementation of development has been running optimally. 2) Community participation in implementing village autonomy This has been going well; this is indicated by the opportunity to participate in development activities and the emergence of awareness and willingness to participate.